Surface Matters: Nanotechnology in Orthopaedics and Spine (Journal of Pakistan Orthopaedic Association, 2023)
Implant surface geometry is important for biological response from surrounding tissue smooth surface to rough to nano-surface have variable response – from cellular and protein adsorption and bony integration, as one changes surface from macro to micro to nano. For stability at bone implant or bone on bone (fracture or graft healing). The surface is important consideration which is modified through osteo-immune cells – macrophages M1&M2 which help in bio-debridement then restore the bone biology and continuity.       Nanotechnology in orthopedics is hot and emerging topic for research and development. Implants as Total Hip Replacement /Total Knee Replacement etc. are now increasingly by coated with nanomaterial as Titanium (Ti) and Hydroxyapatite (HA) which result in better bondage, integration with host bone thus increasing stability and longevity of implant, thus reducing long term complications of loosening etc.